Grazing‐incidence transmission X‐ray scattering: surface scattering in the Born approximation. (18th January 2013) - Lu, Xinhui; Yager, Kevin G.; Johnston, Danvers; Black, Charles T.; Ocko, Benjamin M.
Abstract : Determination of the three‐dimensional order in thin nanostructured films remains challenging. Real‐space imaging methods, including electron microscopies and scanning‐probe methods, have difficulty reconstructing the depth of a film and suffer from limited statistical sampling. X‐ray and neutron scattering have emerged as powerful complementary techniques but have substantial data collection and analysis challenges. This article describes a new method, grazing‐incidence transmission small‐angle X‐ray scattering, which allows for fast scattering measurements that are not burdened by the refraction and reflection effects that have to date plagued grazing‐incidence X‐ray scattering. In particular, by arranging a sample/beam geometry wherein the scattering exits through the edge of the substrate, it is possible to record scattering images that are well described by straightforward (Born approximation) scattering models.